2016
DOI: 10.18632/oncotarget.7219
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta as a prognostic factor in breast cancer patients: A systematic review and meta-analysis

Abstract: BackgroundThe prognostic role of estrogen receptor beta (ERβ) in early-stage breast cancer is unclear. We performed a systematic review and meta-analysis to evaluate the prognostic value of ERβ in early-stage breast cancer patients.MethodWe searched Medline, Embase, and the Web of Science for studies published between 1990 and 2015 that assessed ERβ status in breast cancer patients. A total of 25 studies comprising 9919 patients fitting our inclusion and exclusion criteria were included. The hazard ratios of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
2
27
0
3
Order By: Relevance
“…A positive correlation of ESR1 with age, in addition to the higher ESR1 expression in postmenopausal patients observed in this study both reflect the current view that the prognosis of the patients with ER+ breast cancer should be distinguished by the menopausal status …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A positive correlation of ESR1 with age, in addition to the higher ESR1 expression in postmenopausal patients observed in this study both reflect the current view that the prognosis of the patients with ER+ breast cancer should be distinguished by the menopausal status …”
Section: Discussionsupporting
confidence: 86%
“…epigenetic events such as miRNA expression or protein stabilization).In summary, the present study demonstrates that the downregulation of certain efflux pumps in the tumours of patients with high grade (ABCA9/10) or with poor DFS (ABCG2) has prognostic importance for ER+ breast carcinomas, similar to what was recently demonstrated in patients with ovarian carcinoma 35. A positive correlation of ESR1 with age, in addition to the higher ESR1 expression in postmenopausal patients observed in this study both reflect the current view that the prognosis of the patients with ER+ breast cancer should be distinguished by the menopausal status 36.…”
supporting
confidence: 90%
“…27HC causes conformational change in both the ERα and ERβ [2], and ERβ is known to be expressed in both ERα-positive and ERα-negative tumors [16] as observed in the current study (16.5% of ERβ-positive tumors were ERα/PR-negative). A higher proportion of ERβ-positive tumors were Bcl-2-low; prior studies have evaluted associations between tumor hormone receptor status and Bcl-2 expression, and expression of ERβ or Bcl-2 as prognostic markers [28][29][30][31][32]. The lack of association between other breast cancer characteristics observed in the current study is in line with previous studies [33,34], though an association between ERβ expression and lower-tumor grade has been reported, as have significant associations between ERβ and ERα, between ERβ and PR, and between ERβ and HER2 expression (all p < 0.01) [16].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our result, some previous studies have also suggested for the role of hormone receptors in the molecular pathogenesis of TC. Sex steroid receptors were found in human thyroid tissue, several TC cell lines, and ER levels were significantly higher in TC compared with normal thyroid tissue [1719], which have shown the possibility that ER or PR signaling might represent common etiological factors in the development of TC and BC. Other studies have shown that estrogen could up-regulate the expression of cell cycle-related genes and proto-oncogene in thyroid cells, which were likely to contribute to the development of TC [20].…”
Section: Discussionmentioning
confidence: 99%